PENGARUH PERENCANAAN PAJAK, BOARD DIVERSITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN: (Studi Pada Perusahaan Manufaktur Sub Sektor Barang Konsumsi Yang Terdaftar Di BEI Tahun 2016-2018) - Pristiwantiyasih Pristiwantiyasih (Media Mahardhika, 2020)
This study aims to determine the effect of tax planning, board diversity and good corporate governance simultaneously on the value of the consumer goods sub-sector manufacturing companies listed on the IDX 2016-2018. The sampling technique was using purposive sampling technique. From the partial test results or the t test, from the test results the Tax Planning variable has an influence on Firm Value, because from the results of the t test the calculated t value of the Tax Planning variable is greater than the t table value and the significant value is less than 0.05. While the Board Diversity (DW) variable and the Institutional Ownership variable have no influence on the Firm Value variable, from the test results of these two variables the calculated t value is smaller than the t table value and the significance value is greater than 0.05. The Adjusted R Square value is 0.575. This means that 57.5% of the firm value variable can be explained by tax planning, female directors and institutional ownership. While the remaining 42.5% can be explained by other factors outside the independent variable.